2007
DOI: 10.1093/intimm/dxm002
|View full text |Cite
|
Sign up to set email alerts
|

Follicular exclusion of autoreactive B cells requires Fc RIIb

Abstract: In non-autoimmune mice, the 3H9 transgenic Ig heavy chain can pair with endogenous Iglambda1 light chains to generate B cells with specificity for DNA. These autoreactive cells are actively regulated in vivo, as indicated by the exclusion of lambda1 cells from the splenic B cell follicle and the absence of auto-antibody production. To study the role of Fcgamma receptor IIb (FcgammaRIIb) in peripheral B cell tolerance, FcgammaRIIb(-/-) mice were crossed with C57BL/6 mice bearing a site-directed knock-in of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 34 publications
4
25
0
Order By: Relevance
“…These findings may reflect that autoantibodies against mildly modified LDL particles are more beneficial than those recognizing severely modified forms of LDL. The importance of the inhibitory FcgRIIB in modulating B cell activity and humoral tolerance is supported by studies in both mice and humans (42)(43)(44). In line with these studies, we observed increased amount of splenic B cells and higher levels of plasma autoantibodies recognizing oxidized LDL in the absence of FcgRIIB.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings may reflect that autoantibodies against mildly modified LDL particles are more beneficial than those recognizing severely modified forms of LDL. The importance of the inhibitory FcgRIIB in modulating B cell activity and humoral tolerance is supported by studies in both mice and humans (42)(43)(44). In line with these studies, we observed increased amount of splenic B cells and higher levels of plasma autoantibodies recognizing oxidized LDL in the absence of FcgRIIB.…”
Section: Discussionsupporting
confidence: 86%
“…The Ab pattern, showing higher levels of predominantly oxidized LDL-specific IgG2a/c autoantibodies, as well as increased levels of total IgG2a/c, in our hypercholesterolemic mouse model transplanted with FcgRIIBdeficient BM cells, is well in agreement with the hypothesis that atherosclerosis is driven by Th1 immune responses. Furthermore, the elevated levels of autoantibodies reflect findings in previous studies reporting that FcgRIIB controls BM plasma cell persistence and that absence of the receptor results in autoantibody production and unsatisfactory follicular exclusion of autoreactive B cells (43,44).…”
Section: Discussionsupporting
confidence: 83%
“…Because these B cells were skewed toward being CD21 Ϫ CD23 Ϫ (Table II), they may be composed of memory B cells and/or preplasmablasts. Expansions of similar populations of B cells have been noted in other autoimmune mouse models (28,29). Consistent with this, sorted B220 int I-A b-int B cells from Tg-homozygous mice tended to elaborate more ANAs in culture (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Specifically, the B cell migration pattern into the follicular regions of the spleen can alter the tempo and frequency of T-B cell contact and thus has been proposed as one mechanism to regulate the development of autoreactive B cells (1, 2). Early studies by Cyster et al (3) showed that under conditions of clonal selection, anergic B cells failed to enter the follicular areas, instead arresting at the T-B cell boundary in a process known as follicular exclusion.…”
mentioning
confidence: 99%